Mood profiling during Olympic qualifiying judo competition: A case study testing transactional relationships - Stevens, M. J.; Lane, A. M.; Terry, P. C. (Journal of Sports Science & Medicine, 2006)
This case study investigated relationships between personality, mood states changes, coping strategies, self-set goals, and self-efficacy in an elite judo player. A transactional perspective of psychological responses over time was used to guide data analysis. The ambient mood is proposed to contribute to the interpretation of, and reaction to, events during competition, which lead to subsequent emotional responses. A male international Judo player completed a number of self-report measures before and during a 4-contest tournament. Measures included the EPQ, MCOPE, Brunel Mood Scale, self-set goals, and self-efficacy for goal attainment. State measures were completed after every contest. Results indicated high scores of self-efficacy to achieve performance goals and outcome goals. Pre-competition mood results indicated high scores on the Vigor and Anger subscales with moderate scores for Tension, and zero scores for Depressed mood, a mood profile that remained relatively stable after winning his first two contests. After losing his third contest, he reported symptoms of Depressed mood and indicated using self-blame as coping strategy during the contest. Before the fourth contest, he coped by using planning and increasing effort. These coping strategies were associated with reductions in Depressed mood and increases in Vigor. After finding out his next contest was against a former World Championship bronze medalist, self-set goals became performance and process with no outcome goal. On losing this contest, scores on the Anger and Depression subscales increased sharply, Fatigue scores increased slightly and Tension and Vigor reduced. Self-blame was used as a coping strategy when experiencing unpleasant emotions. Findings suggest that self-blame was associated with negative psychological states comprising depressed mood. Increasing effort and planning were associated with positive psychological states. Collectively, findings emphasize the value of using a transactional design to explore mood changes over time, and future research should investigate the effectiveness of applied interventions.